New low-temperature NMR studies establish the presence of a second equatorial: apical isomer of [(R,S)-Binaphos](CO)2RhH - Castillo Molina, Dante Alberto; Casey, Charles P.; Müller, Imke; Nozaki, Kyoko; Jäkel, Christoph (Organometallics, 2010)
The important enantioselective hydroformylation catalyst [(R,S)-Binaphos](CO)2RhH has been reexamained by low-temperature NMR spectroscopy. Both 1H and 31P NMR spectroscopy at −90 °C allow direct observation of a mixture of two apical−equatorial chelates. The major chelate, 1eq,ap, was shown to have an equatorial phosphine and an apical phosphite. Its structure was unambiguously assigned using low-temperature 31P NMR spectroscopy with selective decoupling of aromatic hydrogens but not of the rhodium hydride, which showed a 225 Hz trans phosphite to RhH coupling. The equilibrium constant for [1eq,ap]/[1ap,eq] was determined over a wide temperature range.
Gesehen am 03.05.2023
Im Titel ist die Zahl 2 nach "CO" tiefgestellt